Corporate Risk Disclosure Trends in South Africa During the Covid-19 Pandemic - OSMAN, Shazia; BALDVOO, Kiran (International Journal of Environmental, Sustainability, and Social Science, 2023)
The novel Covid-19 pandemic created uncertainty around the world. Users now require more information about risk exposure; this paper explored the risk disclosure pattern of South African listed companies during the Covid-19 pandemic. The phenomenon of corporate risk disclosure was explored through a multi-theoretical lens, including agency, legitimacy, and stakeholder theories, given the multi-faceted nature of risk reporting. A content analysis of the annual reports of a sample of non-financial companies listed on the Johannesburg Stock Exchange (JSE) was conducted before and during the Covid-19 pandemic from 2019 to 2021. 84 annual reports were analyzed to determine the extent of corporate risk disclosure, both voluntary and mandatory. A self-developed disclosure index of 25 risk items distributed over three risk categories was used to establish the quantity of corporate risk disclosure. A clear upward trend in the extent of corporate risk disclosure was noted during the Covid-19 pandemic. Given the importance of risk information for decision-making in uncertain times, this study sought to provide an understanding of risk disclosure behavior in South Africa during the initial stage of the pandemic, for which there is limited extant literature. Where extant corporate risk disclosure studies have been conducted in the context of developing economies, this study's findings can be extended to other emerging countries. This study provides the first analysis of the extent of corporate risk disclosure in South Africa during the pandemic. The study's findings are relevant to information users, companies, government, regulatory bodies, and academics.